Toward improving internet navigation for visually impaired screen Reader users: Co-designing an open-source assistive technology system. - Nino, Juan; Kiss, Jocelyne; Poncet, Frédérique; Wittich, Walter; Edwards, Geoffreyjen; Morales, Ernesto (Assistive Technology, 2026)
Visually impaired individuals, estimated at 285 million globally, rely heavily on-screen readers for internet access. However, much of the visually available information, such as the relationship between webpage elements, does not translate well to its textual representation and must be always kept in memory, limiting contextual interactions. To address this challenge, we developed Touch Matrix Assistive Technology Navigator (TOMAT), an open-source system that works alongside screen readers to provide an interactive, audio-tactile representation of webpage structure and enable contextual interactions. Our study employed a participatory design approach, involving visually impaired users, healthcare professionals, engineers, and community organizations in co-design sessions, prototype demonstrations, and focus groups. The resulting system extracts and presents non-linear web information at multiple levels of detail, allowing users to dynamically adjust granularity and efficiently navigate and interact with web content. Participants reported that TOMAT enhanced their understanding of webpage structure and provided an intuitive complement to screen reader software. The findings suggest TOMAT has the potential to improve the internet navigation experience for visually impaired users, fostering greater independence and digital participation. To support further development and collaboration, TOMAT's source files have been released under an open-source license.